FOOD SECURITY OF UKRAINE'S POPULATION UNDER WARTIME CONDITIONS: CHALLENGES AND ADAPTATION MECHANISMS (INNOVATIVE ECONOMY, 2026)
Artimonova I.V., Kyryshun D.V. FOOD SECURITY OF UKRAINE'S POPULATION UNDER WARTIME CONDITIONS: CHALLENGES AND ADAPTATION MECHANISMSPurpose. The study aims to examine the impact of the Russian Federation's full-scale military aggression on the state of food security of Ukraine's population, to identify the principal challenges facing the agri-food system under martial law, and to assess the adaptation mechanisms of the food system implemented by state institutions and international partners.Methodology of research. A complex of general scientific and specialized methods of scientific knowledge was used in the research process. Theoretical generalizations were conducted using methods of analysis and synthesis, induction and deduction, as well as systemic, logical, structural and functional approaches. Economic and statistical methods, comparative analysis, time-series analysis, and the generalization of statistical data from the State Statistics Service of Ukraine, international organizations, FAO, WFP, and analytical materials of the KSE Institute were applied to assess the impact of hostilities on the functioning of the agri-food system, production and export of agricultural products. The method of logical generalization of research findings was employed in formulating conclusions and practical recommendations.Findings. The key consequences of the full-scale military aggression of the russian federation for the functioning of Ukraine's agri-food system and the provision of food security have been identified. It is established that hostilities have adversely affected all segments of the agri-food chain ‒ production, processing, logistics, export, domestic distribution, and population access to food. It is substantiated that the key destabilizing factors include the destruction of production and logistics infrastructure, the mining of agricultural land and the blockade of seaports, labour shortages, rising production costs, and the contraction of export opportunities. It is demonstrated that Ukraine's agricultural sector has exhibited a high degree of adaptability through the diversification of logistics routes, the utilization of alternative export channels, the implementation of state support programs, and the mobilization of international humanitarian and financial assistance. It is determined that the formation of a new food supply model requires strengthening the strategic food reserve system, developing war-risk insurance mechanisms, supporting small and medium-sized agribusinesses, and intensifying international cooperation in the area of food security assurance.Originality. The theoretical and applied approach to examining the impact of war-related risks on the functioning of the agri-food system and ensuring the state's food security has been further developed. The interrelationship between military, logistical, economic, and social factors and the resilience of Ukraine's food system has been identified. The necessity of forming an adaptive food policy model oriented toward enhancing the agri-food sector's resilience to military, economic, and climatic challenges has been substantiated.Practical value. The obtained results of the findings lie in their applicability by state authorities and local self-government bodies in shaping food security policy, developing agricultural sector support programs, and restoring agri-food infrastructure. Specific provisions of the study may be utilized to improve state support mechanisms for agricultural producers, to establish a strategic food reserve system, to develop logistics infrastructure, to expand humanitarian assistance programs, and to introduce war-risk insurance mechanisms in agriculture.Key words: food security, food system, agricultural sector, martial law, food supply, logistics infrastructure, agricultural export, agricultural insurance, state regulation, adaptation mechanisms.
Keywords: food security; food system; agricultural sector; martial law; food supply; logistics infrastructure; agricultural export; agricultural insurance; state regulation; adaptation mechanisms